A reproducible genetic transformation system for cultivated Phaseolus acutifolius (tepary bean) and its use to assess the role of arcelins in resistance to the Mexican bean weevil - Zambre, M; Goossens, A; Cardona Mejía, César; Montagu, M. van; Terryn, N; Angenon, G (Springer, 2005)
A reproducible Agrobacterium tumefaciens-mediated genetic transformation method that delivers fertile and morphologically normal transgenic plants was developed for cultivated tepary bean (Phaseolus acutifolius L. Gray). Factors contributing to higher transformation efficiencies include (1) a low initial concentration of bacteria coupled with a longer cocultivation period with callus, (2) an initial selection of callus on a medium containing low levels of the selectable agent, (3) omission of the selectable agent from the medium during callus differentiation to shoots and (4) the efficient conversion of transgenic shoots into fertile plants. All plants regenerated with this procedure (T0) were stably transformed, and the introduced foreign genes were inherited in a Mendelian fashion in most of the 33 independent transformants. Integration, stable transmission and high expression levels of the transgenes were observed in the T1 and/or T3 progenies of the transgenic lines. The binary transformation vectors contained the ?-glucuronidase reporter gene, the neomycin phosphotransferase II selectable marker gene and either an arcelin 1 or an arcelin 5 gene. Arcelins are seed proteins that are very abundant in some wild P. vulgaris L. genotypes showing resistance to the storage insect Zabrotes subfasciatus (Boheman) (Coleoptera, Bruchidae). Transgenic beans from two different cultivated P. acutifolius genotypes with high arcelin levels were infested with Z. subfasciatus, but they were only marginally less susceptible to infestation than the non-transgenic P. acutifolius. Hence, the arcelin genes tested here are not major determinants of resistance against Z. subfasciatus.